SOYBEAN SUPPLY CHAIN IN PIAUI: AN ANALYSIS OF GRAIN LOSS AS A FUNCTION OF THE DISTANCES DRIVEN - Medeiros, P. O.; Nääs, I. de A. (Revista Brasileira de Engenharia de Biossistemas, 2016)
Soybean is the main oilseed grown and marketed in the world, and it is used as a raw material to supply the agro-industrial complex. In Brazil, most of the soybean production is carried out by road transportation, in particular on the roads from the producer units to the agroindustry processing plant. This study aimed to analyze the losses in soybean transport in two micro-regions of Piaui and to verify if the distance trailed impacted in the volume of grain loss. Information related to 403 truckloads of soybean transported by road from the two farms to the processing agroindustry was collected during April and May 2015. The weight in the origin of the freight and the final destination was recorded, and the weight loss was calculated as the difference between the value registered at the farm and the value recorded at the processing plant. The mean values were analyzed, and the Odds ratio was applied to establish a relationship of cause and effect with the transportation distance and the quantity of grain loss. The results indicate that the path with less distance presented higher grain loss.